2023
DOI: 10.1007/s00232-023-00280-2
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Lymphatic Drug Delivery Vehicles as a New Avenue for Targeted Therapy: Lymphatic Trafficking, Applications, Challenges, and Future Horizons

Abstract: Lymphatic drug targeting is an effective approach for targeting immunomodulators, and chemotherapeutic drugs at a specific organ or cellular location. The cellular, paracellular, and dendritic cell trafficking machinery are involved in the lymphatic transport of therapeutic agents. The engineering of triggered and hybrid lymphatic drug delivery systems (LDDS) is a promising strategy to fight cancer metastasis and microbial pandemics. Hybrid lymphatic drug delivery systems can be tailored and developed by graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 186 publications
1
7
0
Order By: Relevance
“…Therefore, the presence of a free carboxylic group could be the main contributor to erythrocyte hemolysis. In our previous study, it was found that administration of GFT at the reported dose produced a serum level below 2 µg/mL (Harisa, Sherif, & Alanazi, 2023). Moreover, the in vivo study showed that serum obtained from blood samples was clear with no notable hemolysis.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, the presence of a free carboxylic group could be the main contributor to erythrocyte hemolysis. In our previous study, it was found that administration of GFT at the reported dose produced a serum level below 2 µg/mL (Harisa, Sherif, & Alanazi, 2023). Moreover, the in vivo study showed that serum obtained from blood samples was clear with no notable hemolysis.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, cancer cells escaped from the primary site (breast) to secondary organs through the lymphatic system which exaggerates the rate of death (Sherif et al, 2022b). The escaped cancer cell could be entrapped within the lymph nodes where it is considered a key sponsor of relapse following the completion of therapy (Harisa, Sherif, & Alanazi, 2023). Consequently, there is an urgent demand to establish effective approaches to overcome the developed resistance and rerouting the administered therapeutic agents to the lymphatic system (Yaghoubi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, encapsulating anticancer agents within a drug delivery system capable of reaching the lymphatic system and overcoming resistance offers a promising approach to improve patient outcomes. This is attributed to the reported cancer relapse, where detached cancer cells are hidden within the lymph nodes of the lymphatic system [19] and can enter systemic circulation following therapeutic protocols, leading to the formation of new masses in systemic organs [20].…”
Section: Introductionmentioning
confidence: 99%